Dead man's ransom - Peters, Ellis, 1913-1995 (Peters, Ellis, 1913-1995. Cadfael chronicles, 1997)
In the midst of a twelfth-century civil war between King Stephen and Empress Maud, a hostage exchange is put in jeopardy when one of the prisoners dies, and Brother Cadfael determines that he was murdered.